Prevalence of varicocoele and its association with body mass index among 39, 559 rural men in eastern China: a population‐based cross‐sectional study. (May 2017) - Liu, J.; Zhang, S.; Liu, M.; Wang, Q.; Shen, H.; Zhang, Y.; Yan, D.
Summary: Varicocoele is a common cause of male infertility. We undertook a population‐based cross‐sectional study to evaluate the prevalence of varicocoele among rural men in eastern China and its association with body mass index. A total of 39, 559 rural men in six counties in Beijing, Guangdong and Shandong provinces were recruited from 2011 to 2012. The presence and severity of varicocoele were measured by physical examinations. Univariate and multivariate logistic regression models were constructed to assess the association between varicocoele and body mass index after adjusting for possible confounders. Varicocoele was diagnosed in 1911 of 39, 559 participants with an overall prevalence of 4.83%. The prevalence of varicocoele was highest in underweight (6.29%) and lowest in obese patients (3.71%, p < 0.05). The prevalence also decreased as body mass index increased in all three varicocoele grades. In multivariate logistic regression analysis after adjusting for region, age, height, occupation, cigarette smoking and alcohol consumption, body mass index was still inversely and independently associated with varicocoele ( p < 0.001). Compared with normal weight men, underweight men (OR = 1.34; 95% CI, 1.10–1.63) were more likely to have varicocoele, whereas overweight men (OR = 0.88; 95% CI, 0.79–0.99) and obese men (OR = 0.75; 95% CI, 0.58–0.97) were less likely to have varicocoele. This study revealed that the prevalence of varicocoele was 4.83% among rural men in eastern China; body mass index was inversely and independently associated with the presence of varicocoele. Future efforts should be made to validate the risk factors for varicocoele and strengthen the prevention and treatment of varicocoele, especially in underweight men.